Analysis of the role of autophagy inhibition by two complementary human cytomegalovirus BECN1/Beclin 1-binding proteins. Issue 2 (1st February 2016) - Mouna, Lina; Hernandez, Eva; Bonte, Dorine; Brost, Rebekka; Amazit, Larbi; Delgui, Laura R.; Brune, Wolfram; Geballe, Adam P.; Beau, Isabelle; Esclatine, Audrey
ABSTRACT: Autophagy is activated early after human cytomegalovirus (HCMV) infection but, later on, the virus blocks autophagy. Here we characterized 2 HCMV proteins, TRS1 and IRS1, which inhibit autophagy during infection. Expression of either TRS1 or IRS1 was able to block autophagy in different cell lines, independently of the EIF2S1 kinase, EIF2AK2/PKR. Instead, TRS1 and IRS1 interacted with the autophagy protein BECN1/Beclin 1. We mapped the BECN1-binding domain (BBD) of IRS1 and TRS1 and found it to be essential for autophagy inhibition. Mutant viruses that express only IRS1 or TRS1 partially controlled autophagy, whereas a double mutant virus expressing neither protein stimulated autophagy. A mutant virus that did not express IRS1 and expressed a truncated form of TRS1 in which the BBD was deleted, failed to control autophagy. However, this mutant virus had similar replication kinetics as wild-type virus, suggesting that autophagy inhibition is not critical for viral replication. In fact, using pharmacological modulators of autophagy and inhibition of autophagy by shRNA knockdown, we discovered that stimulating autophagy enhanced viral replication. Conversely, inhibiting autophagy decreased HCMV infection. Thus, our results demonstrate a new proviral role of autophagy for a DNA virus.